THU0631 Incidence of Serious Adverse Events in Patients with Rheumatoid Arthritis Exposed To Biologic Therapies. Results from Biobadabrasil Registry. (15th July 2016) - Ranza, R.; Laurindo, I.; Titton, D.; Bertolo, M.; Bianchi, W.; Brenol, C.; Bustamante, M.; Carvalho, H.; Castro, G.; Costa, I.; Duarte, A.; Fernandes, V.; et al.
Abstract : Background: The safety profile of biologic drugs might have substantial regional differences. Since 2009, the Brazilian Society of Rheumatology runs BiobadaBrasil, a registry for monitoring of biologic therapies in rheumatic diseases, in collaboration with other Latin America countries (BiobadaAmerica) and with Biobadaser Objectives: To report the incidence of serious adverse events (SAE) in Rheumatoid Arthritis (RA) patients exposed to biologic drugs in Brazil Methods: BiobadaBrasil counts on thirty two centers, from almost all Brazilian states, that prospectively include patients with active rheumatic diseases who started a biologic drug or a synthetic DMARD as a parallel control group. A constant three level monitory of data quality is maintained (online, by phone and "in situ"). This study focuses on SAE (for definition: Protocolo 1.1 at https://biobadaser.ser.es/biobadamerica/Brasil/cgi-bin/upload/documentacion.aspx ) in RA patients exposed to biologics from January 2009 to June 2015. Time of exposure was set from start of the drug to the date of last administration or censorship. Continuous variables were expressed as mean with standard deviation (SD). SAE incidence rate was calculated per 1000 patient/years with 95%CI Results: Out of a total of 1649 subjects with RA, 1121 were exposed to biologics (4735 p/y), 91% a-TNFs, follow-up 2.8 (2.2) yrs, 85% females, at baseline: age 50 (14) yrs, disease duration 9 (8) yrs, DAS28 5.4 (1.4). Controls were 528 (1971 p/y), follow-up 3.6 (2.2) yrs, 86% females, at baseline: age 54 (13) yrs, disease duration 6 (8) yrs, DAS28 5.1 (3.1). The incidence rates of SAE in the biologics and control groups were 86 [78, 94] vs 34 [27, 44] (ratio 2.5 [1.9, 3.3], p<0.001). There was no statistical difference in SAE incidence between a-TNFs and non-a-TNF biologics. Among a-TNFs, Adalimumab was associated with less SAE (64 [53, 79]) compared with Etanercept (93 [77, 113] p<0.01) and Infliximab (102 [86, 122] p=0.0003). SAE were more frequent with subsequent a-TNF than with the first, 107 [87, 132] vs 79 [70, 90] (ratio 1.4 [1.1, 1.7] p=0.0078). Among SAEs with biologics, serious infections account for half of the events (43 [37–49]) Conclusions: In the BiobadaBrasil registry the incidence of SAE is 2 fold higher with biologics than with synthetic DMARDs, and higher with subsequent a-TNF than with the first Acknowledgement: for data monitoring P Cabral, for contributing to BiobadaBrasil registry, L.Barbosa, W.Chahade, A.Hayata, A.Kakehasi, M.Pinheiro, A.Ranzolin, M.Scheinberg, F.Sztajnbok, I.Silveira Disclosure of Interest: None declared